(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2013)
Thomas Gray in his Poetry zeroes in at humanism. There are certain characteristics of humanism which are abundantly found in poetry of Thomas Gray. Some of them are found in his odasmelancholy, morality, humanity, humility, sympathy, rapport, pity and pathos, are some salient features which are found throughout his poetical work. All these things constitute humanism. The humanistic ideas are so dashed with the moralizing notes or didacticism that the combined effect is attractive to a very high degree. The gist of Gray’s is to satirize the artidicial society that cannot resist the charm of gold and gaiety.Gray’s Poetry is packed with many a human value which gray presents before us to be imbibed. He thinks that childhood is free from all sorts of mistakes which are committed by the grownups. Childhood is the only state of life that remains free from selfishness, jealousy, ambition, partiality, pride, temptation, abhor, and many other social evils.Gray lies worried about those people who become victims of problems and miseries and no one helps or solves their problems. After childhood everyone becomes so busy that he does not even think of help and co-operation or commiseration. It is nothing else but inhumanity if a man does not solve problems of others, and reduce the sufferings and pains of the people.Solving of problems and reducing suffering and pains of the people with help of reason is more important than religious beliefs. This typer of attitude of Gray reveals humanism in his poetry